BASIC CONCEPTS OF GROUP COUNSELING - Bakhrudin All Habsy; Ayu Anggraini; Fataya Layyinatul Fuad; Tri Cahyo Nugroho; Ummu Zahroh (Jurnal Kajian Pendidikan dan Psikologi, 2026)
Group counseling is one of the implementations of responsive service program strategies from a series of comprehensive guidance and counseling programs in schools in the form of providing professional assistance to each individual in a group who has similar problems. The meaning of the main and fundamental concept of group counseling lies in how a guidance and counseling teacher can develop and overcome the problems of group members in accordance with predetermined provisions so that it becomes a benchmark for the success of group counseling sessions. This research aims to provide an understanding through a concrete explanation of the basic concepts of group counseling which become the foundation in the implementation of group counseling services so that there is an optimal success of counseling results. The result of this research is an explanation of the basic concepts of group counseling which includes understanding, objectives, principles, procedures, benefits, and challenges in group counseling services. The method used in this research is a qualitative method of literature study, understanding of a fact or phenomenon through the process of collecting data from various sources such as books, journals, and existing research by conceptualizing and understanding the text objectively and rationally. The basic concept of group counseling is very important because it is used as the first step in the implementation and realization of guidance and counseling programs.